1999
DOI: 10.5980/jpnjurol1989.90.911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging and Diseases on Male Sexual Function Assessed by the International Index of Erectile Function

Abstract: Aging and chronic disorders that have been considered to be putative risk factors for ED, therefore affect male sexual function in the elderly. The IIEF was suggested to be suited for use in studies assessing epidemiology of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…9 In a Japanese study, Marumo et al reported that DM was a risk factor for ED. 6 In this study, DM is an independent risk factor of ED in male HD patients. DM is thought to be a risk factor of ED, not only in the general population but also in dialysis patients.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…9 In a Japanese study, Marumo et al reported that DM was a risk factor for ED. 6 In this study, DM is an independent risk factor of ED in male HD patients. DM is thought to be a risk factor of ED, not only in the general population but also in dialysis patients.…”
Section: Discussionmentioning
confidence: 59%
“…9 In the Japanese population, Marumo et al reported that hypertension and heart disease were putative risk factors for ED. 6 Because most of the dialysis patients had hypertension and heart disease, hypertension and heart disease were not independent risk factors in dialysis patients in this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a previous study, mean ± standard deviation IIEF scores for EF, OF, SD, IS and overall satisfaction (OS) for diabetic men aged in their 50s were 9.6 ± 8.1, 3.8 ± 4.0, 4.7 ± 2.0, 2.3 ± 3.9 and 5.6 ± 1.6, respectively. In contrast, these scores for non‐diabetic men aged in their 50s were all higher at 21.3 ± 9.5, 7.4 ± 3.5, 6.4 ± 2.2, 7.4 ± 4.4 and 6.8 ± 2.3, respectively 4 …”
Section: Chronic Diseasesmentioning
confidence: 95%
“…The effects of aging on male sexual function were investigated in 967 male employees (aged 22–59 years) of 10 Japanese companies, using the International Index of Erectile Function (IIEF) questionnaire 4 . In subjects who were free from risk factors for sexual function (i.e.…”
Section: Agingmentioning
confidence: 99%